Hubungan Kepatuhan Menjalani Terapi Hemodialisis dengan Kualitas Hidup Pasien Penyakit Ginjal Kronik di Masa Pandemi Covid-19 - Susantri, Wella; Bayhakki, Bayhakki; Woferst, Rismadefi (Holistic Nursing and Health Science, 2022)
Introduction : The COVID-19 pandemic became one of the highest causes of death in early 2020. The spread is so fast and uncontrollable that it is the reason for many people to stay at home and avoid places with the highest spread, one of which is the hospital. In this condition, many people delay treatment, choose alternatives, and decide to no longer be in the hospital environment. This also applies to patients with chronic kidney failure, where sufferers are required to continue to take therapy to achieve a good quality of life. However, with the COVID-19 situation, most sufferers postpone therapy so they don't get infected. Compliance with therapy is very important for people with CKD to be able to achieve a good quality of life. This study aims to determine the relationship between compliance with hemodialysis therapy and the quality of life of CKD patients undergoing hemodialysis therapy during the COVID-19 period. Method: The research design used is descriptive correlational with a cross sectional approach. The sample in this study was a total sampling of 70 respondents. This study used the KDQL questionnaire to measure quality of life and The End-Stage Renal Disease Adherence Questionnaire (ESRD-AQ) questionnaire to measure adherence. The analysis used was bivariate analysis using the chi-square test. Results: Iit was found that 71.4% adhered to hemodialysis therapy and, 54.3% have a good quality of life. The statistical test results showed that there was a significant relationship between adherence to hemodialysis therapy and the quality of life of CKD patients where the p-value was 0.026 < α (0.05). Conclusion: There is a significant relationship between adherence and quality of life of CKD patients undergoing hemodialysis therapy. Nurses have an important role in motivating CKD patients to comply with hemodialysis therapy.Keywords: Hemodialysis Therapy, Adherence, Quality of Life, Chronic Kidney Disease.